Analisis Pengadaan Barang di PT Waskita Beton Precast - Syaina Ulfah Azhara; Heru Winarno; Faisal Ibnu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Procurement of goods has a very important role for an organization, because obtaining the goods needed to fulfill the mission of the organization with a significant budget. So that companies will always try to act professionally and strive to continue to develop different innovations in order to achieve goals and aspirations. The Make to Order method is a process in which the company will carry out production when orders come from consumers, this method has been implemented by PT. Waskita Beton Precast. in running the production process. The direct procurement system is used to provide satisfaction to consumers because there is no need to wait a long time to complete consumer requests. Companies must adjust to production needs so as not to leave unused items. Procurement of goods to meet during production activities can be brought in according to the needs of the company. From the direct procurement method used by the company, it has a good impact, the production process is on schedule and is not hampered by the arrival of the goods needed during the production process and can complete consumer requests in a timely manner.